Palimpgestos sonoros em Araçá azul - Gama, Mariana Mazoti (2023)
Caetano Veloso's work is recognizably innovative, especially in the context of Tropicalism, a period marked by the search for a new expression through experimentation in the arts. This is the keynote that drives the Araçá Azul album, probably the most radical work by the composer from Bahia, bearing in mind the elements of Vanguarda aesthetics from the beginning of the 20th century, both from Europe and Brazil, notably in the sound aspect. In this perspective, the present research sought to question the extent to which the poetic fabric of Araçá Azul would expand and/or overcome the experimental proposal of these vanguards. The main objective was to understand the language of Araçá Azul from the perspective of experimentalism, and the specifics: to identify the dialogue between Araçá Azul and the Vanguard aesthetics of the early 20th century, notably concerning the Modernism of 22 (anthropophagy), to the Movement of Concrete Poetry and Tropicalism, and analyze some lyrics from the album Araçá Azul. To this end, it mobilized the concept of voice and performance, from Paul Zumthor, of Antropofagia, from Oswald de Andrade, in addition to the Vanguard Theory, by Peter Bürger, and sound perspective, from José Miguel Wisnik. As for the methodological procedures, the work was divided into three chapters, the first being dedicated to the aesthetic and historical context of Vanguarda aesthetics, fundamental to understanding the production of the Araçá Azul album, the second dealt with the conceptual deepening, and the third aimed at the analysis of some songs on the album. Araçá Azul not only expands, but also surpasses the avant-garde proposal of the Modernist, Concretist and Tropicalist movements insofar as the analysis of the songs points to the methodological proposal aiming at self-anthropophagy as a procedure, especially in the dialogue between noise and silence present in some songs , which makes it a sound palimpgest. It is hoped, in this way, to contribute to the dialogue between literary studies and other arts, taking into account the richness of such articulation.